Too Cold, Too Hot, or Just Right? : Assessing Financial Sector Development Across the Globe - Barajas, Adolfo (IMF Working Papers; Working Paper ;, 2013)
This paper introduces the concept of the financial possibility frontier as a constrained optimum level of financial development to gauge the relative performance of financial systems across the globe. This frontier takes into account structural country characteristics, institutional, and macroeconomic factors that impact financial system deepening. We operationalize this framework using a benchmarking exercise, which relates the difference between the actual level of financial development and the level predicted by structural characteristics, to an array of policy variables. We also show that an overshooting of the financial system significantly beyond levels predicted by its structural fundamentals is associated with credit booms and busts.